Measurement of the average very forward energy as a function of the track multiplicity at central pseudorapidities in proton-proton collisions at √s=13TeV - KAYA, MİTHAT (My University, 2019)
© 2019, CERN for the benefit of the CMS collaboration.The average total energy as well as its hadronic and electromagnetic components are measured with the CMS detector at pseudorapidities - 6.6 < η< - 5.2 in proton-proton collisions at a centre-of-mass energy s=13TeV. The results are presented as a function of the charged particle multiplicity in the region | η| < 2. This measurement is sensitive to correlations induced by the underlying event structure over a very wide pseudorapidity region. The predictions of Monte Carlo event generators commonly used in collider experiments and ultra-high energy cosmic ray physics are compared to the data. All generators considered overestimate the fraction of energy going into hadrons.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)